Project management workbook and PMP/CAPM exam study guide - Kerzner, Harold (Hoboken, N.J. : J. Wiley & Sons, 2009)
Project Management Workbook And Pmp (R)/Capm(R) Exam Study Guide The Leading project management workbook--and an unparalleled PMP(R) /CAPM(R) Exam study guide Now updated and revised in a Tenth Edition, this powerful two-in-one resource
Project management overview -- Project management growth : concepts and definitions -- Organizational structures -- Organizing and staffing the project office and team -- Management functions -- Management of your time and stress -- Conflicts -- Special topics -- The variables for success -- Working with executives -- Planning -- Network scheduling techniques -- Project graphics -- Pricing and estimating -- Cost control -- Trade-off analysis -- Risk management -- Learning curves -- Contract management -- Quality management -- Modern developments in project management -- Situational exercises -- Project management crossword puzzles -- PMP and CAPM exam review -- Project management logic problems
1
Keywords: Project management -- Problems, exercises, etc; project management -- Examinations -- Study guides; Project management -- Examinations, questions, etc